2020
DOI: 10.4103/meajo.meajo_195_19
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for retinopathy of prematurity in Tabuk city, KSA

Abstract: PURPOSE: Retinopathy of prematurity (ROP) is becoming a leading cause of preventable blindness. The current study aimed to assess ROP and its risk factors in Tabuk City, Northern Kingdom of Saudi Arabia. METHODS: A retrospective study was conducted in King Khalid Hospital, Tabuk City, Saudi Arabia. The premature infants' records during the period of January 2016 to April 2018 were approached. One hundred and eight records were eligible; the infants' gestational age, wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…Arabia [19] Of the patients in this study, 33.3% were diagnosed with ROP. The gestational age was 32 weeks or less in 91.7% of the cases, and 72.2% of patients had a birth weight reported between 1,000 g and 1,500 g.…”
Section: Saudimentioning
confidence: 81%
“…Arabia [19] Of the patients in this study, 33.3% were diagnosed with ROP. The gestational age was 32 weeks or less in 91.7% of the cases, and 72.2% of patients had a birth weight reported between 1,000 g and 1,500 g.…”
Section: Saudimentioning
confidence: 81%
“…4 A similar percentage of infants diagnosed with ROP (33.3%) was reported in a study from Tabuk. 5 The major risk factors are gestational age and birth weight. Additionally, using supplemental oxygen in preterm infants, respiratory distress, and blood transfusion are considered common risk factors of ROP.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a multicenter trial on 4099 preterm infants revealed that 65.8% of the infants developed ROP, and 81.6% of those who weighed less than 1000 g [ 3 ]. Regarding the etiology of ROP, the major risk factors for the disorder are low birth weight (BW), low gestational age (GA), and oxygen therapy [ 4 - 6 ]. In addition, several studies have suggested that blood transfusions, mechanical ventilation, and sepsis are the other factors that contribute to an increased incidence of ROP in premature infants [ 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%